Over a century later and 400 kilometers apart: rediscovery of Bulbophyllum barbatum (Orchidaceae) in Diamantina, Minas Gerais, Brazil - L. F. Menezes, Euler; C. O. Giordani, Samuel; S. Rosim, Mauro; Gonella, Paulo M. (Phytotaxa, 2022)
Fieldwork focused on the Orchidaceae family from the Diamantina Plateau of the Espinhaço Range in Minas Gerais, Southeast Brazil, resulted in the rediscovery of Bulbophyllum barbatum almost 140 years after its original description, in 1882. The species, known only from the original illustration by Barbosa Rodrigues, was originally described from the region known as Zona da Mata Mineira, and its rediscovery is reported from over 400 km to the northwest of that region. The new record allowed a more detailed study of its morphology, the first photographs of the species, as well as the preliminary assessment of its conservation status as Critically Endangered. Such unexpected rediscovery highlights the importance of conservation actions in the Brazilian campos rupestres given its high diversity and endemism, the deficient knowledge on the taxonomy and distribution of its species, and the increasing pressure of human activities.